Analysis of Factors Affecting Travelers' Decisions in Choosing Online Ticket and Flight Purchases - Habibie, Fachrul Husain; Gantina, Devita; Al Rasyid, Yuliansyah; Adsena, Yogi Priya; Pangkerego, Eduard Rudolf (Jurnal Penelitian Pariwisata, 2025)
This study aims to analyze the factors influencing tourists' decisions to purchase flight tickets and hotel accommodations online, focusing on the role of trust and previous tourist experiences. The research uses a quantitative approach with path analysis to test the direct and indirect effects of trust and tourist experience on purchase decisions. A sample of 200 respondents who have purchased online tickets was selected using purposive sampling. Data were collected through online questionnaires, and the analysis was conducted using various statistical tests, including validity, reliability, and path analysis. The results show that trust has a significant impact on both tourist experience and purchase decisions. Furthermore, tourist experience acts as a moderating variable, strengthening the relationship between trust and purchase decisions. Positive experiences with online ticket platforms enhance trust and increase the likelihood of purchasing, while negative experiences reduce trust and hinder purchase decisions. The study concludes that trust in online platforms significantly influences tourist decisions to purchase tickets and accommodations, and previous experiences play a crucial role in moderating this effect. It is recommended that tourists choose trustworthy platforms with secure transactions and clear information. Travel app managers should focus on improving service quality, transparency, and security to foster trust and enhance user loyalty, ultimately increasing purchase decisions. Keywords: trust, tourist experience, purchase decision